Study on the Glass Silicon Anodic Direct Bonding Parameters - Li Jia; Guo Hao; Guo Zhiping; Miao Shujing; Wang Jingxiang (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
By MEMS packaging test platform for bonding process of bonding temperature and bonding time, and test silicon specifications experimental study. Experimental results indicate that when the bonding voltage of 1200V, bonding temperature of 4450C to 4550C, bonding time is 60s,the void fraction is less than 5%.Glass and silicon wafer bonding quality can achieve the best. The experimental results in order to improve the glass silicon bonding quality provide the basis.